Who benefits most from college? Dimensions of selection and heterogeneous returns to higher education in the United States and the Netherlands. (June 2021) - Forster, Andrea G.; van de Werfhorst, Herman G.; Leopold, Thomas
Abstract: There has been ample debate about heterogeneous returns to a college degree, and so far, findings have been mixed on the question of whether individuals who attend college are also those who benefit most from it (positive selection), whether returns would be larger for those who never went (negative selection), or whether there is heterogeneity in returns at all. We argue that these diverging findings have two sources: First, they may arise from different conceptualizations of selection into college. We argue that different selection mechanisms have to be distinguished. We separate the college selection process into two meaningful dimensions, one capturing school-irrelevant factors related to social origin and the other capturing school-relevant factors related to individual capabilities. We, then, study heterogeneous returns to a college degree for the two dimensions separately. Second, the structure of the educational system and the labor market might contribute to different patterns of returns to college. We study heterogeneous returns to a college degree in the United States and the Netherlands, two countries with strong differences in how education and labor market are structured. Overall, we find returns to college to be rather homogeneous instead of heterogeneous. For the school-relevant dimension of selection, we do see a tendency towards positive selection for US-men and a tendency towards negative selection for US-women. For the Netherlands, we find that returns are truly homogeneous.